A spontaneous anterior fusion of lumbar spine after posterolateral lumbar fusion with pedicle screw-plate system - Chaiwat Kraiwattanapong; Issara Chandrsawang; Gun Keorochana; Panupol Rajinda; Pongsthorn Chanplakorn; Pittavat Leelapattana; Umaporn Udomsubpayakul; Thamrong Lertudomphonwanit (BMC Musculoskeletal Disorders)
Abstract Background Lumbar posterolateral fusion (PLF) with Pedicle Screw-Plate (PSP) fixation without interbody fusion found spontaneous anterior fusion (SAF). No study has reported the SAF of lumbar spine in patients who underwent PLF. This study reports the rate of SAF of lumbar spine after PLF with PSP system compared with the rate of SAF after PLF with pedicle screw-rod (PSR) system. Methods Retrospective reviews of charts and radiographs were performed in 111 patients who underwent PLF with PSP system and PSR system for treatment of degenerative lumbar spine. Demographic data, diagnosis, Meyerding grading, level of fusion, Pfirrmann grading, disc height, pedicle screw depth, follow-up time and SAF were compared between PSP and PSR groups. Results Fifty-five patients in the PSP group and 56 patients in the PSR group were included with similar baseline characteristics. There were more degenerative spondylolisthesis patients in the PSP group compared with patients in the PSR group. However, there was no significant difference of Pfirrmann grading in both groups. Fifteen patients (27.3%) in the PSP group developed SAF while no patient in the PSR group had SAF. When patients in the PSP group were analyzed, the mean follow-up time in patients with SAF was significantly longer than the no SAF group. Conclusion This study has reported SAF of lumbar spine in patients who underwent PLF with the PSP system. The SAF increasingly occurred with longer follow-up time. In this study, no SAF was found in patients who underwent PLF with the PSR system.